2016
DOI: 10.1111/desc.12399
|View full text |Cite
|
Sign up to set email alerts
|

Parietal hyper‐connectivity, aberrant brain organization, and circuit‐based biomarkers in children with mathematical disabilities

Abstract: Mathematical disabilities (MD) have a negative life-long impact on professional success, employment, and health outcomes. Yet, little is known about the intrinsic functional brain organization that contributes to poor math skills in affected children. It is now increasingly recognized that math cognition requires coordinated interaction within a large-scale fronto-parietal network anchored in the intraparietal sulcus (IPS). Here we characterize intrinsic functional connectivity within this IPS-network in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
74
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 84 publications
14
74
3
6
Order By: Relevance
“…Consistent with this view, greater IPS connectivity with the dlPFC, vlPFC and insula has previously been found in children with math disabilities. 58 Notably, in contrast to the findings from the present longitudinal study spanning 6 years, a cross-sectional study of 2nd and 3rd grade children (ages 7-8 to [8][9] found no changes in IPS connectivity over the period of 1 year. 59 Thus, the characterization of longitudinal growth trajectories over a longer time interval are necessary for detecting selective weakening of parietal-prefrontal circuits with age.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this view, greater IPS connectivity with the dlPFC, vlPFC and insula has previously been found in children with math disabilities. 58 Notably, in contrast to the findings from the present longitudinal study spanning 6 years, a cross-sectional study of 2nd and 3rd grade children (ages 7-8 to [8][9] found no changes in IPS connectivity over the period of 1 year. 59 Thus, the characterization of longitudinal growth trajectories over a longer time interval are necessary for detecting selective weakening of parietal-prefrontal circuits with age.…”
Section: Discussioncontrasting
confidence: 99%
“…[38][39][40][41] Furthermore, deficits in number sense are associated with irregularities in parietal structure and function. Individuals with dyscalculia are shown to have decreased gray matter, [42][43][44][45] atypical patterns of neural activation during the number comparison task, 46 and altered functional connectivity of parietal structures both at rest 47 and during arithmetic problem solving. 48 In addition to correlational studies, some research has attempted to provide causal support for the role of parietal mechanisms in processing numerical information.…”
Section: The Case For a Link Between Number Sense And Symbolic Numerimentioning
confidence: 99%
“…4). Compared to their typically developing peers, children with MD show aberrant IPS connectivity with multiple prefrontal and parietal regions (Jolles et al, 2016). Specifically, children with MD show greater functional connectivity between left and right IPS, as well as between IPS and dorsolateral and ventrolateral PFC.…”
Section: Parietal–frontal Working Memory Systemsmentioning
confidence: 99%